Is ketamine efficacious for rapid treatment of acute suicidal ideation in an emergency setting? Lessons learned from a pilot randomized controlled trial - Maryam Barzkar; Kaveh Alavi; Kazem Malakouti; Mohamad-Amin Khajeh-Azad; Farzaneh Barzkar; Amir Hossein Jalali Nadoushan; Mohammad Niakan Lahiji (BMC Research Notes)
Abstract Objective This study aimed to evaluate the efficacy of a single infusion of ketamine in inducing rapid remission of severe suicidal ideation, compared to Midazolam, in a population with acute suicidal thoughts. In a double-blind randomized controlled trial conducted in Tehran, Iran, from January to July 2022 (IRCT20220118053756N1), 36 inpatients with acute severe suicidal ideation were enrolled. Participants were randomly assigned to receive either a single dose of ketamine (0.5 mg/kg) or Midazolam (0.02 mg/kg). Suicidality was assessed using the Beck Scale for Suicide Ideation (BSSI) and the Suicide-Visual Analog Scale (S-VAS) before the intervention and at 12 and 24 h post-administration. Results At baseline, the Midazolam group exhibited significantly higher BSSI scores and a higher rate of borderline personality disorder than the Ketamine group. Mean BSSI and S-VAS scores at 12 and 24 h after the treatment decreased significantly compared to baseline in both groups. Despite these observations, no statistically significant differences were found between the groups in terms of BSSI and S-VAS scores. Trial registration The protocol for this RCT was registered at the Iranian Registry of Clinical Trials (IRCT). The trial registration details are as follows: IRCT registration number IRCT20220118053756N1, with the registration date being June 12, 2022 (1401/03/22). It is important to note that this trial was retrospectively registered.